(untitled) (Journal Of Educational and Psychological Researches, 2016)
Interest in the teaching profession is one of the most important steps on the road to education reform to develop the quality of education is not only through the teacher’s professional competencies required, interest in the teaching profession in any society stems from fingerprints left by the teacher on his behavior and morals and their minds and their personalities. Today we are going to provide scientific, technical and research is enormous, we need more powerful skills and ways of thinking that must be acquired by the teacher. The current search is gaining importance in terms of: This is the first of its kind on the researcher’s knowledge _ which deals with the modern trends in the teaching of home economics, the researcher hopes that fills a gap in the educational field and utilized in other studies serve the domestic economy materials Improving teaching quality by highlighting the strategy may be unknown to many teachers, and highlighted motivation may help to try and benefit from advantages. the researcher presented in chapter third some creative teaching strategies that the students experience and research results have shown their effectiveness in raising academic achievement for students.